Gaya Kepemimpinan Kepala Madrasah dalam Meningkatkan Kompetensi Pedagogik Guru Madrasah Ibtidaiyah Musi Rawas di Sumatera Selatan - Lilis Merlita; Hermansyah Hermansyah; Vera Nopianti; Kardiyo Kardiyo; Adisel Adisel (Al-Khair Journal: Management Education, 2024)
Abstract: The leadership style of the head of madrasah ibtidaiyah is still difficult to demonstrate the pedagogic competence of teachers, characterized by pedagogic competence is still mechanical and students tend to be dwarfed. The purpose of this study is to map and analyze the leadership style of madrasah heads in improving the pedagogic competence of madrasah ibtidaiyah Musi Rawas Sumatera Selatan. Using a descriptive qualitative method. Data collection techniques through observation, interviews, and documentation. The data analysis technique is similar to Hubermen's theory through data reduction, data presentation, and conclusion drawn. The results of the study show that the leadership of the head of the madrasah has applied a democratic leadership style in improving the competence of teachers, such as the leadership style has upheld togetherness, improved teachers' essential skills in learning management, motivated teachers, provided opportunities to participate in further education, training, seminars, and workshops, applied discipline and supervised classes. Therefore, it can be concluded that the leadership style of the head of the madrasah can improve the pedagogic competence of teachers. So it can be suggested, to improve the pedagogic competence of teachers, then improve the leadership style of madrasah heads in madrasas.Keywords: Leadership Style of Madrasah Heads, Pedagogic Competence of Teachers, Madrasah Ibtidaiyah. Abstrak: Gaya kepemimpinan kepala madrasah ibtidaiyah masih sulit mewujukan kompetensi pedagogic guru, ditandai dengan kompetensi pedagogik masih mekanis dan siswa cenderung kerdil. Tujuan penelitian ini untuk memetakan dan menganalisis gaya kepemimpinan kepala madrasah dalam meningkatkan kompetensi pedagogik guru madrasah ibtidaiyah Musi Rawas Sumatera Selatan. Menggunakan metode kualitatif deskriptif. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Teknik analisis data mirip teori Hubermen melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepemimpinan kepala madrasah telah menerapkan gaya kepemimpinan demokratis dalam meningkatkan kompetensi pedaogik guru, seperti gaya kepemimpinan telah menjunjung tinggi kebersamaan, meningkatkan keterampilan esensial guru dalam pengelolaan pembelajaran, memotivasi guru, memberikan kesempatan untuk mengikuti pendidikan lanjutan, pelatihan, seminar, dan workshop, menerapkan disiplin dan melakukan supervisi kelas. Oleh karena itu, dapat disimpulkan bahwa gaya kepemimpinan kepala madrasah dapat meningkatkan kompetensi pedagogik guru. Sehingga dapat disarankan, untuk meningkatkan kompetensi pedagogic guru, maka tingkatkan gaya kepemimpinan kepala madrasah di madrasah. Kata kunci: Gaya Kepemimpinan Kepala madrasah, Kompetensi Pedagogik Guru, Madrasah Ibtidaiyah.